NATAL, VILA OR CIDADE? - Teixeira, Rubenilson Brazão (Mercator, 2019)
In the studies that deal with the history of the city of Natal, capital of Rio Grande do Norte, Brazil, there are contradictory assertions about the urban status it received when it was founded in 1599. For some authors, it emerged as a vila (village); for others, as a cidade (city), two categories of urban settlements included in the Portuguese urban terminology of that period. In this work, we show that it is possible to decide clearly in favor of one of these assertions based upon the analysis of a series of historiographic and documentary evidences and other considerations. Keywords : Natal, village, city, foundation, terminology, municipal power.